EFFECT OF COPING EFFORTS ON THE TREATMENT BEHAVIOR OF PATIENTS WITH PULMONARY TUBERCULOSIS - Ronald Mbulu; Muhammad Bagus Qomaruddin; Oedojo Soedirham (Jurnal Berkala Epidemiologi, 2020)
Background: Pulmonary tuberculosis has a huge impact on the lives of patients—physically, economically, and socially—and can thus cause stress. Prolonged stress can cause illness and affect one's health behavior, so that it requires proper coping efforts such as management problems and emotional regulation so that adaptive health behavior can be formed. Purpose: The aim of this study was to analyze the effect of coping efforts (problem management and emotional regulation) on the treatment behavior of patients with lung tuberculosis in the city of Surabaya using the theoretical approach of transactional stress and coping. Methods: This study was an observational study with a cross-sectional design conducted in 13 Public Health Center (PHC) in Surabaya with the highest number of new cases of positive acid resistant bacteria of tuberculosis (TB-BTA+) with 229 populations. The sampling technique used was simple random sampling and found 142 respondents, with the inclusion criteria being patients with pulmonary TB who were undergoing treatment in the first quarter. The data collection used a questionnaire, and the data analysis was performed using logistic regression. Results: This study found that there was an influence of problem management (p = 0.01; prevalence ratio [PR] = 1.36; 95% confidence interval [CI] = 1.04 < PR < 1.78) on treatment behavior, while the emotional regulation variable and the characteristic variable did not influence treatment behavior. Conclusion: The results of this study showed that patients with pulmonary TB who performed good coping efforts formed good treatment behavior.